Jornadas formativas mediadas por tecnologias digitais no ensino superior: aportes para pensar atividades assíncronas - Mill, Daniel (2022)
The aim of this article is to encourage reflections and pedagogical initiatives that are appropriate to the educational context induced by the pandemic moment in which we have been immersed since the beginning of 2020. In the text, we analyse a possible setting for teaching-learning activities in virtual learning environments (VLE), in a perspective of flipped classroom, blended, active and meaningful learning. The analysed experience articulated synchronous activities (web conferences) and asynchronous activities (VLE), but in this article the purposeful effort turned to the analysis and discussion of the composition and adequacy of appropriate environments for asynchronous activities. As a result, some contributions are presented to think and carry out asynchronous pedagogical activities that are coherent with formative journeys in pandemic times.